Country Club, Trinidad - (:unkn) unknown (My University, 2009)
A picture of a man with a lady outfitted in tennis clothing, walking away from the main entrance of the Trinidad Country Club, Long Circular Road, Port of Spain. The club was established in 1931. The land on which it stands was part of the large colonial estate - Champs Elysées.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Clubs--Trinidad and Tobago; Architecture--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Trinidad Country Club